2013
DOI: 10.5178/lebs.2013.24
|View full text |Cite
|
Sign up to set email alerts
|

Unintentional Unfair Behavior Promotes Charitable Donation

Abstract: Recent studies have demonstrated that people inflict self-punishment after unintentionally making an unfair allocation decision. The present study examined whether or not the unfair allocation decision would also prompt participants to make a charitable donation. The results indicated that participants who unintentionally made an unfair allocation decision donated a greater amount of money than those who made a fair allocation decision. In addition, the amount of money that participants donated was positively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…As we stated in the introduction section, the state shame score was indistinguishable from the state guilt score. As shown in Table 1, only shame-proneness predicted post-transgression state shame and guilt (for similar results, see Giner-Sorolla et al, 2011;Ohtsubo & Watanabe, 2013). The lack of significant correlation between guilt-proneness and state guilt might be attributable to the experimental procedure (i.e., no chance of reconciliation) that deemphasized the role of guilt.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…As we stated in the introduction section, the state shame score was indistinguishable from the state guilt score. As shown in Table 1, only shame-proneness predicted post-transgression state shame and guilt (for similar results, see Giner-Sorolla et al, 2011;Ohtsubo & Watanabe, 2013). The lack of significant correlation between guilt-proneness and state guilt might be attributable to the experimental procedure (i.e., no chance of reconciliation) that deemphasized the role of guilt.…”
Section: Resultsmentioning
confidence: 65%
“…After omitting this participant, self-punishment was correlated with shame proneness at a marginally significant level, r (47) = .24, p < .10. To confirm the reliability of the result, we also combined this dataset with previous datasets (Ohtsubo & Watanabe, 2013; Watanabe & Ohtsubo, 2012, Study 3) after standardizing the self-punishment scores within each experiment. The correlation between shame-proneness and self-punishment was significant, r (144) = .18, p = .030…”
Section: Resultsmentioning
confidence: 99%
“…Liu and Aaker () found that priming a donation appeal with an initial request for volunteering time, “How much time would you like to donate to the American Cancer Society?” (p. 546), engaged an emotional mindset—as contrasted with a mindset focused on money and economic utility—and consequently generated more donations at the end of the experiment. Similarly, others have found that experimentally inducing emotions, such as sadness (Kandrack & Lundberg, ), guilt (Darlington & Macker, ; Ohtsubo & Watanabe, ), or anger (Kandrack & Lundberg, ) prior to a charitable request increased donations. Simply displaying the word “love” (Guéguen & Lamy, ) or a heart shape (Guéguen, Jacob, & Charles‐Sire, ) increased donations in field experiments.…”
Section: Literature Reviewmentioning
confidence: 86%
“…However, Krishna (2011) argues prosocial spending may function differently in the case of purchasing cause-related products, as the purchase may be perceived as an egoistic act, and therefore not increase happiness. Another study found evidence of increased giving as a method of guilt reduction (Ohtsubo & Watanabe, 2013).…”
Section: Altruism Altruistic Values and Warm Glowmentioning
confidence: 99%